Evaluation of the therapeutic efficacy of rumen transfaunation. Issue 1 (31st October 2019) - Steiner, Simone; Linhart, Nina; Neidl, Anita; Baumgartner, Walter; Tichy, Alexander; Wittek, Thomas
Abstract: Transfaunation is supposed to stimulate normal rumen function and has been used as an ancillary treatment for indigestion. Although it is widely recommended, there are little research data on the efficacy and the necessary volume. The objective of the prospective clinical trial was the evaluation of the therapeutic efficacy of two different transfaunation volumes which can be obtained under practical conditions. Forty‐five cattle suffering from indigestion were included in the study. A scoring system for the classification of rumen fluid was used. Scores were given in accordance with the importance of the parameter as an indication of microbial dysfunction. Animals with disturbed rumen fluid composition and activity were randomly assigned into 3 groups. Group 1 received 1 L of rumen fluid, group 2 received 5 L of rumen fluid and group 3 (control group) received 5 L of body temperature water. Rumen fluid analysis was repeated on days 1 and 4 after transfaunation. The feed intake of the animals was recorded. After the transfaunation of 1 L and 5 L, the rumen fluid score improved significantly from day 0 to days 1 and 4. Rumen fluid samples in the control group showed no significant improvement from day 0 to day 1. No significant differences were observed between the two treatment groups. But significant differences between the improvement of group 1 and the control group on days 1 and 4 and significant differences between group 2 and the control group on day 1 were detected. Small volumes of rumen fluid are easily obtainable by stomach tubes fitted with suction pumps. In summary, the transfaunation of as little as 1 L of rumen fluid caused significant improvement in the activity of rumen flora in cows suffering from indigestion.